Philanthropy to Corporate Social Responsibility: An Indian Perspective - Sweta SINGH (Revista de Management Comparat International)
Purpose – Corporate social responsibility (CSR) involves corporations, states, international organizations and civil society organizations. It has emerged as a global trend. The various concerns regarding CSR includes: what CSR stands for, what the trend really is, where it comes from, where it is heading and who the leading actors are. And these issues are still far from clear. The purpose of this paper is to examine the trend of CSR in all its complexity and look forward in the potential impact and major concerns related to it. Design/methodology/approach – Combined analysis of central documents and publications on CSR with analysis of articles related to CSR. Findings – Apart from defining and explaining the various issues related to CSR, the paper throws further insights in the prevalent trends of CSR in various corporate in India. Originality/value – The conceptual explanations shows the likely development and potential impact of a corporate social development. Moreover, the discussions help us reflect on the formation of management trends.